COMPARATIVE ANALYSIS OF INDONESIAN HOUSEHOLD CONSUMPTION EXPENDITURE 2018-2021 - Haribowo, Rio; Irwan Moridu,; M. Rafid,; Karnawi Kamar,; Muhammad Yusuf, (Journal of Innovation Research and Knowledge, 2022)
The purpose of this study to discuss about comparative analysis of Indonesian household consumption expenditure 2018-2021. This type of research is included in descriptive research. The data taken in this study used secondary data. Indonesian household consumption expenditure data from 2018 to 2021. The data analysis technique in this research uses descriptive qualitative. The research results show that even though it had experienced a deep contraction in 2020, expenditure for household consumption that is leisure and lifestyle experienced positive growth in 2021 of 2.97 percent. This shows that there has been a fairly good recovery during 2021